Synthesis, crystal structure, and Hirshfeld surface analysis of 3-ferrocenyl-1-(pyridin-2-yl)-1H-pyrazol-5-amine - Delara Joekar; Lana K. Hiscock; Louise N. Dawe (Acta Crystallographica Section E: Crystallographic Communications, 2023)
A key step towards utilizing polynuclear metal-based systems in magnetic device applications involves the careful design of ligands. This strategic planning aims to produce metal assemblies that exhibit some kind of `switch' mechanism. Towards this end, a ligand that incorporates a redox-active functional group (ferrocene) is reported. This communication presents the multi-step synthesis, characterization (1H and 13C NMR), and structural analysis (single-crystal X-ray diffraction and Hirshfeld surface analysis) of 3-ferrocenyl-1-(pyridin-2-yl)-1H-pyrazol-5-amine, [Fe(C5H5)(C13H11N4)]. Supramolecular features, including π–π stacking and hydrogen bonding are quantified, while a database search reveals the unique combination of molecular moieties, which offer future opportunities for studies to involve simultaneous Lewis acid and base coordination.